Outcomes Research in Cardiovascular Imaging: Report of a Workshop Sponsored by the National Heart, Lung, and Blood Institute - Douglas, Pamela S. (2009)
In July of 2008, the National Heart, Lung, and Blood Institute convened experts in noninvasive cardiovascular imaging, outcomes research, statistics, and clinical trials to develop recommendations for future randomized controlled trials of the use of imaging in: 1) screening the asymptomatic patient for coronary artery disease; 2) assessment of patients with stable angina; 3) identification of acute coronary syndromes in the emergency room; and 4) assessment of heart failure patients with chronic coronary artery disease with reduced left ventricular ejection fraction. This study highlights several possible trial designs for each clinical situation.